Chris Petersen for City Council Fundraiser at Butler Hall Park - Watkins, Howard::::::::: (1985)
Howard Watkins, Paul Pierce, Darren Belk, Chris Petersen, Audrey Krause, Dallas Blanchard, ?,Patrick Young, Chris Petersen